Novalis Schriften: die Werke Friedrich von Hardenbergs - Novalis 1772-1801; Kluckhohn, Paul 1886-1957; Samuel, Richard 1900-1983; Mähl, Hans Joachim 1923-2001; Schulz, Gerhard 1928-2022 (Darmstadt Wissenschaftliche Buchgesellschaft, 1965)
Novalis's philosophical writings are often grounded in nature. His works explore how personal freedom and creativity emerge in the affective understanding of the world and others. He suggests that this can only be accomplished if people are not estranged from the earth. In Pollen, Novalis writes "We are on a mission: Our calling is the cultivation of the earth", arguing that human beings come to know themselves through experiencing and enlivening nature. Novalis's personal commitment to understanding one's self and the world through nature can be seen in Novalis's unfinished novel, Heinrich von Ofterdingen, in which he uses his knowledge of natural science derived from his work overseeing salt mining to understand the human condition. Novalis's commitment to cultivating nature has even been considered as a potential source of insight for a deeper understanding of the environmental crisis.
Band 3: Das philosophische Werk II
Georg Philipp Friedrich Freiherr von Hardenberg (1772-1801), better known by his pen name Novalis, was an 18th-century German aristocrat, poet, author, mystic and philosopher of Early German Romanticism.
2 of 6 vols.
Includes bibliographical references.
Keywords: 18th Century (1701-1800); Philosophy; Germany